2001
DOI: 10.1002/jsl.3000180302
|View full text |Cite
|
Sign up to set email alerts
|

Base fluid parameters for elastohydrodynamic lubrication and friction calculations and their influence on lubrication capability

Abstract: In this study, base fluid parameters for elastohydrodynamic lubrication (EHL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Film thickness is essentially established in a low-pressure region at the inlet side of the contact, whereas traction, for the most part, is generated by the shearing of the film in the high-pressure Hertz region of contact. The pressure-viscosity coefficient, a, quantifies the film-generating capability of a lubricant in tribological contacts at isothermal conditions [3,4]. This coefficient is very dependent on the chemical structure of the base oil [3,5,6] and could be modified using small quantities of additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Film thickness is essentially established in a low-pressure region at the inlet side of the contact, whereas traction, for the most part, is generated by the shearing of the film in the high-pressure Hertz region of contact. The pressure-viscosity coefficient, a, quantifies the film-generating capability of a lubricant in tribological contacts at isothermal conditions [3,4]. This coefficient is very dependent on the chemical structure of the base oil [3,5,6] and could be modified using small quantities of additives.…”
Section: Introductionmentioning
confidence: 99%
“…The pressure-viscosity coefficient, a, quantifies the film-generating capability of a lubricant in tribological contacts at isothermal conditions [3,4]. This coefficient is very dependent on the chemical structure of the base oil [3,5,6] and could be modified using small quantities of additives. The universal pressure-viscosity coefficient, a film , defined by Bair et al [7] quantifies the general piezoviscous response relevant to Newtonian concentrated contact film forming.…”
Section: Introductionmentioning
confidence: 99%
“…Yokoyama and Spikes explored the film-forming properties of polyol esters, polyphenyl ethers, and their mixtures over a wide range of temperature [25]. Larsson et al studied a few base fluid parameters for elastohydrodynamic lubrication and friction calculations, and investigated their influences on lubrication capability [26]. Lord and Larsson reported the effects of slide-roll ratio and lubricant properties of a synthetic ester VG46 on elastohydrodynamic lubrication film thickness and traction, and suggested that the ester maintained a relatively thicker lubricant film during sliding than did the corresponding polyalphaolefin and mineral oils [27].…”
Section: Introductionmentioning
confidence: 99%
“…These values do not give enough information to choose the optimum lubricant for a lubricated contact [3]. In mec7hanical systems take place rolling, sliding and rolling/sliding contacts, therefore lubricants have to work the best possible in these operation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid wear, it is necessary to keep the lubricant film thick enough to prevent any contact between the surfaces. Friction should be minimised in order to obtain as high efficiency as possible and pressure peaks should be as small as possible to avoid large sub-surface stresses and thus avoid pitting fatigue [3]. An equation that describe the influence of some parameters in lubricant film is the Hamrock-Dowson one (Equation 1) for elliptical conjunctions.…”
Section: Introductionmentioning
confidence: 99%